Subject Analysis, Content Analysis and Domain Analysis: Concepts, Methods and Applications - Alves Silva Portella, Tauany Lorena; de Lima, Gercina Ângela (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
From the perspective of the constant increase in data and information, consider in Library and Information Science that the correct analysis and representation of the contents of documents analyzed in specific domains is essential for the retrieval, organization, and dissemination of information. Subject Analysis categorizes topics and details, making it easier to retrieve relevant information. Domain Analysis studies specific characteristics of a field of knowledge, comprising terminologies and concepts. Content Analysis identifies and analyzes textual elements, deepening the understanding of documentary content. This study explores these analyses' approaches, techniques, and methodologies, highlighting their often confused interrelationships, differences, and similarities. To achieve the proposed objective to support the conceptual and theoretical-methodological discussion on subject analysis, content analysis, and domain analysis, focusing on their interrelations, differences, and similarities that are often confused in their concepts and methodologies, the research developed an exploratory and descriptive approach, a bibliographic survey was carried out in the BRAPCI database, using the terms "domain analysis", "content analysis" and "content analysis", recovering 134 documents. Results are efficiently defined and applied to each analysis. These analyses guarantee efficient information retrieval, which is vital to growing data volume.